Uso de dietas com grão inteiro para terminação de bezerros de origem leiteira . - Cutrim, Darley Oliveira (Universidade Federal do Tocantins, 2023)
A total of two experiments were conducted to evaluate the effects of pearl millet whole 67 grain, sorghum whole-grain and babassu mesocarp bran (BMB) inclusion in corn 68 whole-grain diets on feed intake and digestibility, carcass and beef performance and 69 characteristics, blood indicators, rumen fermentation parameters and intake behavior 70 super-young dairy cattle finished in confinement. We evaluated four concentrate-only 71 experimental diets named corn diet, a whole-grain corn diet with a pelleted nucleus; 72 babassu diet, a corn-based diet with 100g/kg of BMB; pearl millet diet, a corn-based 73 diet with 316.8g/kg of pearl millet whole grains; and sorghum diet, a corn-based diet 74 with 316.8 g/kg of sorghum whole grains. In experiment 1, we used 25 mixed-breed 75 calves (Holstein x Zebu) which were distributed among the four treatments according 76 to a completely randomized design. Regarding diet digestibility, blood parameters and 77 intake behavior, we evaluated the effects of diets, animal age (3, 6 and 9 months) and 78 diet versus age interaction. The calves’ experimental period began at the age of two 79 months and average corporal weight (BW) of 55.12±2.2 kg and was concluded at the 80 age of 12 months. The babassu diet yielded lower (P<0.05) DM, CP, NDF and TDN 81 that other diets which did not differ among themselves. Calf diet and age had no effect 82 (P>0.05) on DM and CP digestibility. Regarding NFC, the pearl millet diet (0.74) 83 showed lower digestibility than the corn (0.84) and babassu (0.84) diet but did not differ 84 from the sorghum diet (0.78). The animals showed a lower digestibility of the studied 85 diets’ NFC at the age of 9 months compared to the 3 and 6 month old calves. Regarding 86 ADG and final BW, the babassu diet yielded inferior results (P<0.05) than other diets 87 which did not differ among themselves. The highest plasma urea (51.65mg/dL) and 88 creatinine (2.09 mg/dL) levels were found in the babassu diet fed animals. The corn 89 diet and sorghum diet-fed animals showed higher (P<0.05) empty-body weight, hot 90 carcass weight and cold carcass weight compared to the babassu diet-fed animals, 91 while the pearl millet diet-fed calves did not differ compared to the others. The pearl 92 millet diet-fed animals showed lower (P<0.05) HCY (50.2 kg/ 100 kg BW) and CCY 93 (48.5 kg/100 kg BW) compared to the other studied animals. The diets did not influence 94 (P>0.05) the calves’ meat texture, marbling, tenderness, color and chemical 95 composition. The sorghum diet fed animals showed a higher (P<0.10) intramuscular 96 concentration of conjugated linolenic acid (CLA, 0.29 g/100g total FA) than the 97 babassu diet-fed (0.12 g/100 g total FA) and pearl millet diet-fed animals, while the 98 corn diet-fed calves did not differ from the others. Intake behavior of the studied 99 animals was not modified (P>0.05) by their diets. In all diets, the animals had longer 100 (P<0.05) feeding times during the afternoon (18.54%) while the rumination time 101 (18.39%) and resting time (59.99%) were longer during late-night hours. DMFE, 102 DMRUE and NDFRUE increased (P<0.05) with calf age. In experiment 2, eight mixed 103 breed (Holstein x Zebu), ruminally cannulated, six-month-old calves with an initial body 104 weight 160.62 ±4.65 kg were used and distributed in two simultaneous Latin squares 105 (4x4). We evaluated diet intake and digestibility, ruminal short chain fatty acid 106 concentration, ammonia concentration and pH, as well as, blood parameters of calves. 14 107 Regarding OM and NFC digestibility, the corn (OM, 0.78; NHC, 0.85) and babassu 108 (OM, 0.74; NFC, 0.84) diets were superior (P<0.05) were superior to the sorghum (OM, 109 0.65; HFC, 0.69) diet, while the pearl millet diet did not differ from the others. The diets 110 did not have any effect on the calves’ rumen production of short chain fatty acids, 111 ammonia (N-NH3), rumen pH and blood indicators. Rumen acetate, propionate and 112 butyrate concentrations showed a quadratic behavior throughout the day. Pearl millet 113 and sorghum as whole grains can be included in 316 g/kg DM in ruminant corn whole 114 grain diets which modify the metabolism and consequent performance of 10-month 115 old calves. On the other hand, babassu mesocarp bran should not be included in 116 whole-grain diets due to its detrimental effect on diet intake and calf performance.